Rustamid Imamate - Aillet, Cyrille (The Encyclopedia of Empire, 2016)
The Rustamid Imamate (777–909 ce) is still considered the symbol of a vanished Golden Age and the model for an anti‐absolutist and collegial form of government by today's Ibadis. It was also one of the first autonomous Islamic states in North Africa and its capital, Tâhart (northwestern Algeria), achieved prosperity during the 9th century thanks to its pioneering role in trans‐Saharan trade.
Keywords: Dynastie rustumide

الأمن (الشرطة) في عهد الرستميين - بحاز, إبراهيم بن بكير (الحياة, 2016)
Keywords: Dynastie rustumide

الإباضي والآخر تعايش أم احتقان: عينات من العصر الوسيط - بوعقادة, عبد القادر (مجلة كلية الآداب والعلوم الإنسانية, 2016)
Keywords: Dynastie rustumide